Memory of the Ongoing War in Modern Ukrainian Poetry (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
The presented article analyzes selected modern poetic texts about the Russian-Ukrainian war of 2022–2023. It was observed that such poetry appears instantly as a kind of artistic reflection and fixation of the new war reality. It is about different genres and topics: trench lyrics and poetic reporting from the front, refugee poetry, story of a survivor / victim, philosophical meditation and other genres – in traditional rhyming or free verse. Most often, the authors post such poetry on social networks, often not only poets themselves, but also ordinary users record videos with these texts and upload the content to Tik Tok or YouTube (sometimes such video texts gain thousands of views and become “viral”). It is also an established practice when a poetic text becomes a song, and then a hit. Ukrainian war poetry is not only a text, but also media content, which determines its high popularity and recognition. From this point of view, the poetic works of well-known Ukrainian poets – Viktoria Amelina, Ihor Astapenko, Tania Vlasova, Lesia Horova, Borys Humeniuk, Svitlana Didukh-Romanenko, Halyna Kruk, Anna Maligon, Oksana Stomina, Natalka Slobodianiuk, Tetiana Yarovitsyna – were included for analysis.Modern Ukrainian war poetry can be conditionally divided into several thematic layers. First of all, it is about the depiction of the actual war as a battlefield between Russian occupiers and Ukrainian defenders (frontline sketches, portraits of Ukrainian defenders, commemoration of the fallen soldiers). Also, an important part of poetic texts is a reflection of war reality, which is now everyday life for civilian Ukrainians (occupied and de-occupied territories of Ukraine, missiles-bomb terror of peaceful towns and villages, psychosomatics of war, when no one anywhere in Ukraine can feel completely safe). Voices of Ukrainian forced migrants are also an important poetic testimony of tragedy of the ukrainian war. The analysed texts, representing war poetry, formed a whole layer of the national and universal archive. They correlate with the collective memory of Ukrainian people, strengthen its individual moments, highlight the names of heroes, form a kind of poetic monument to all those who suffered from the actual war in Ukraine.
Keywords: memory; archive; memorial; trauma; war; Ukraine